2019
DOI: 10.1123/ijsnem.2018-0201
|View full text |Cite
|
Sign up to set email alerts
|

Energy Availability in Athletics: Health, Performance, and Physique

Abstract: The reported prevalence of low energy availability (LEA) in female and male track and field athletes is between 18% and 58% with the highest prevalence among athletes in endurance and jump events. In male athletes, LEA may result in reduced testosterone levels and libido along with impaired training capacity. In female track and field athletes, functional hypothalamic amenorrhea as consequence of LEA has been reported among 60% of elite middle- and long-distance athletes and 23% among elite sprinters. Health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
2
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(159 citation statements)
references
References 73 publications
4
145
2
8
Order By: Relevance
“…• Large dependency of endogenous fat energy substrate but requires a constant supply of exogenous CHO energy substrate for synergistic energy provisions and prevention of metabolic fatigue Theme 2. Energy Availability in Athletics: Managing Health, Performance, and Physique (Melin et al, 2019) Dietary energy must meet the energy cost of an Athlete's training load and competition program as well as support the body's nonsport function/activities related to health and well-being. The conventional interest in energy targets the concept of energy balance where differences between dietary energy intake and total daily energy expenditure create opportunities for changes in body composition to store or utilize body fat and protein.…”
Section: Recognizing the Special Issues Of Event Groups In Athletesmentioning
confidence: 99%
“…• Large dependency of endogenous fat energy substrate but requires a constant supply of exogenous CHO energy substrate for synergistic energy provisions and prevention of metabolic fatigue Theme 2. Energy Availability in Athletics: Managing Health, Performance, and Physique (Melin et al, 2019) Dietary energy must meet the energy cost of an Athlete's training load and competition program as well as support the body's nonsport function/activities related to health and well-being. The conventional interest in energy targets the concept of energy balance where differences between dietary energy intake and total daily energy expenditure create opportunities for changes in body composition to store or utilize body fat and protein.…”
Section: Recognizing the Special Issues Of Event Groups In Athletesmentioning
confidence: 99%
“…Importantly, it helps the athlete to integrate the inevitability or benefits of brief periods of controlled low energy availability within the endurance training framework. Problems associated with chronic or severe low energy availability, known as relative energy deficiency in sports, are well known (Mountjoy et al, 2018); specific issues in relation to Athletics are covered by Melin et al (2019).…”
Section: Suggested Implementation Of Prerace Low-fiber Dietmentioning
confidence: 99%
“…From the studies examined, 3 out of 7 CS studies and 1 out of 3 RCT studies included female participants, but the results of male only athletes are considered within this review. Clinical LEA (<30 kcal/kg LBM/d) or subclinical LEA (36 ± 6 kcal/kg LBM/d) was prevalent in all of the cross‐sectional studies (Table ). Participants included jockeys, wrestlers, cyclists, and endurance athletes .…”
Section: Resultsmentioning
confidence: 96%
“…Optimal levels of EA are difficult to determine in the athletic population; however, according to Loucks and Thuma, for young and healthy sedentary females, energy balance equals 0 kcal/d when EA = 45 kcal/kg FFM/d (FFM = free fat mass). Research has shown subclinical EA of 44‐30 kcal/kg FFM/d poses no serious threat to physiological responses in female athletes . At present, there is no definitive number to determine LEA, and contrary to what has previously been accepted, recent research from Lieberman et al has shown that EA < 30 kcal/kg LBM/d does not predict menstrual disturbances such as luteal phase defects, oligomenorrhea, and anovulation.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation